(untitled) (Modern education and development, 2024)
The relevance of this topic lies in the development of students’ communicative competence. Students are a typical group of future personnel who must have a special sense of responsibility for their future profession. Many of us encounter nationalities of different languages. Not knowing the language can cause incomplete communication. If a student does not speak the language well, he will not be able to enter into communication and will not have a complete and broad understanding of the information. The reason for such high attention to knowledge of the Russian language is the need for mandatory mastery of not only professional, but also communicative competence.